Calcimimetic restores diabetic peripheral neuropathy by ameliorating apoptosis and improving autophagy. Issue 12 (December 2018) - Chung, You; Lim, Ji; Oh, Hyun; Kim, Hyung; Kim, Min; Kim, Eun; Kim, Yaeni; Chang, Yoon; Kim, Hye; Park, Cheol
Abstract Decreased AMPK-eNOS bioavailability mediates the development of diabetic peripheral neuropathy (DPN) through increased apoptosis and decreased autophagy activity in relation to oxidative stress. Schwann cells are responsible for maintaining structural and functional integrity of neurons and for repairing damaged nerves. We evaluated the neuro-protective effect of cinacalcet on DPN by activating the AMPK-eNOS pathway usingdb/db mice and human Schwann cells (HSCs). Sciatic nerve ofdb/db mice was characterized by disorganized myelin, axonal shrinkage, and degeneration that were accompanied by marked fibrosis, inflammation, and apoptosis. These phenotypical alterations were significantly improved by cinacalcet treatment along with improvement in sensorimotor functional parameters. Cinacalcet demonstrated favorable effects through increased expression and activation of calcium-sensing receptor (CaSR)-CaMKKβ and phosphorylation of AMPK-eNOS signaling in diabetic sciatic nerve. Cinacalcet decreased apoptosis and increased autophagy activity in relation to decreased oxidative stress in HSCs cultured in high-glucose medium as well. This was accompanied by increased expression of the CaSR, intracellular Ca++ ([Ca++ ]i) levels, and CaMKKβ-LKB1-AMPK signaling pathway, resulting in the net effect of increased eNOS phosphorylation, NOx concentration, Bcl-2/Bax ratio, beclin 1, and LC3-II/LC3-I ratio. These results demonstrated that cinacalcet treatment ameliorates inflammation, apoptosis, and autophagy through increased expression of the CaSR, [Ca++ ]i levels and subsequent activation of CaMKKβ-LKB-1-AMPK-eNOS pathway in the sciatic nerve and HSCs under diabetic condition. Therefore, cinacalcet may play an important role in the restoration and amelioration of DPN by ameliorating apoptosis and improving autophagy.